Incorporating metal active centers into covalent organic frameworks for boosting CO2 photoreduction - Ming-zhen, Chen; Hai-rong Zhao; Zhang, Kai-ming; Hong-jing, Zhu; Hai-bao Duan; Xiao-Ming, Ren (Inorganic chemistry frontiers, 2025)
Photocatalytic CO2 reduction into valuable chemical fuels is a highly desirable subject in the field of photosynthesis. Nevertheless, the performance of most current photocatalytic CO2 reduction catalysts remains a significant challenge for practical applications. In this study, we present the achievement of anchoring of nickel (Ni) metal sites onto a flexible and stable covalent organic framework (COF-Tp-Azo) for photocatalytic CO2 reduction. It is noteworthy that the flexibility of the framework plays a crucial role in improving the adsorption of carbon dioxide, as it minimizes steric hindrance. On incorporating varying amounts of metal active species into the COFs, the resultant COF-Tp-Azo-Nix demonstrates a pronounced influence on the catalytic activity. Specifically, COF-Tp-Azo-Ni0.33 exhibits a high CO production rate of 9742.5 μmol g−1 h−1 with a selectivity as high as 98.8% under visible light irradiation, representing the highest production and selectivity for reported nickel-based COFs. The photoelectrochemical experiments demonstrate that the covalent bonding between Ni2+ and COF-Tp-Azo inhibits the recombination of photogenerated charge carriers and facilitates electron migration, thereby enhancing catalytic activity. Additionally, theoretical calculations reveal that the low energy barrier in both the absorption process between Ni-COF-Tp-Azo and CO2, as well as the protonation process for Ni-*COO, contributes to the superior catalytic activity of COF-Tp-Azo-Nix. This work opens a new pathway to high-performance catalysts for CO2 photoreduction.